Effects of poverty on academic performance of undergraduates in Nwafor Orizu College of Education, Nsugbe, Anambra State. (International Journal of Scientific Research and Management (IJSRM), 2024)
The study was aimed at ascertaining the effects of poverty on the academic performance of undergraduates in Nwafor Orizu College of Education, Nsugbe. Three (3) research questions and one (1) hypothesis guided the study. The population of the study is made up of year 2, year 3 and final year B.Ed students of Nwafor Orizu College of Education, Nsugbe, comprising 3, 394 undergraduates. The study used a proportionate random sampling technique to select the sample of the study, to ensure that each school of the six (6) schools in Nwafor Orizu College of Education, Nsugbe was proportionately represented in the population. A total of 300 students were selected as the sample for the study. Questionnaire was used to collect data for the study. In other to ascertain the face and content validity of the instrument, the questionnaire was given to an expert in Economics Department and also two experts in the department of education Measurement and Evaluation for validation. The reliability of the instrument was established using test-retest method. The data collected were analyzed using mean and chi-square. Based on the analysis of the data, the following findings were made that the government and the people, on how to improve the standard of living of the masses more especially the undergraduates in the institutions of higher learning which was as a result of effect of poverty on academic performance of the students. With view to finding out solutions to the problems in order to improve the academic performance and wellbeing of the undergraduates, it was recommended among others that undergraduates will be trained in the institutions, if only the government should help in alleviating economic poverty by providing the undergraduates with all their essential needs both in terms of social, political and economic ways which will go a long way in developing the man power and state at large. Provision of the necessary materials needed by the undergraduates will help in the development of the state.